STABILITAS HARGA IKAN DI KOTA AMBON MELALUI PERAN COLD STORAGE, OPTIMASI PRODUKSI DAN EFISIENSI TEKNIS - Stevanus M. Siahainenia; Dionisius Bawole; Eygner Gerald Talakua (Universitas Pattimura, 2019)
The purpose of this study was to find out the function of cold storage in stabilizing fish prices in Ambon City, analyzing optimal production levels of various types of dominant fish, and analyzing the level of efficiency of utilization of cold storage and auxiliary machinery. This study uses the survey method. Primary data collection through questionnaires is built empirically while secondary data is obtained from several agencies related to this study. The research sample was drawn by exhausting sampling, amounting to 6 cold storage units in Ambon City. The role of cold storage to stabilize fish prices was analyzed using a qualitative descriptive approach, while the quantitative techniques used included analysis of optimization of cold storage production with linear programming and analysis of the efficiency of utilization of cold storage. The results of the study show that cold storage has not played a role properly to stabilize fish prices in Ambon City. To achieve optimal use of production factors, the cold storage management needs to reduce the raw material by 24,915.9 kg / month; 7 HOK / month workforce; cold storage storage space capacity of 2.09 kg / month; and demand for flying fish 1,402.6 kg / month, while the use of production factors efficiently (fully utulized) is the capacity of the freezing machine, demand for tuna, skipjack, and cob. The level of technical efficiency of the utilization of cold storage facilities is reached, the total use of installed capacity must be proportional to the capacity used.